Immunogenicity, safety, and tolerability of a recombinant hepatitis B vaccine manufactured by a modified process in healthy young Japanese adults - Hiroyuki Kishino; Kenichi Takahashi; Miyuki Sawata; Yoshiyuki Tanaka (Taylor & Francis Group, 2018)
Hepatitis B vaccines are highly effective in preventing hepatitis B virus infection and have been included in the national immunization program of Japan since 2016. Heptavax®-II is one of two hepatitis B vaccine products licensed in Japan, and its manufacturing process is being modified to reduce variability of manufacturing and optimize immunogenicity. In this study (NCT01463683), the immunogenicity and safety of a modified-process hepatitis B vaccine (mpHBV) were compared to those of the licensed Heptavax®-II. Overall, 722 Japanese adults aged 20-to-35 years old were randomized in a 3:3:1 ratio to either the mpHBV subcutaneous (SC) injection group (mpHBV SC), the Heptavax®-II SC injection group (Heptavax®-II SC), or the mpHBV intramuscular (IM) injection group (mpHBV IM). All participants received a 3-dose series of either mpHBV or Heptavax®-II at Day 1, Month 1, and Month 6. Serum antibody to hepatitis B virus surface antigen (anti-HBs) was assayed on Day 1 prior to the first vaccination and Month 7 (1 month Postdose 3). Seroprotection rates in mpHBV SC were non-inferior to that in Heptavax®-II SC and anti-HBs geometric mean titers were numerically higher in mpHBV SC as compared to Heptavax®-II SC. The incidences of injection-site and systemic adverse events (AEs) observed in mpHBV SC were comparable to those in Heptavax®-II SC, except for erythema which was higher in mpHBV SC than in Heptavax®-II SC. Most injection-site and systemic AEs were mild-to-moderate in intensity and there were no reports of vaccine-related serious AEs in any group. IM administration of mpHBV was well-tolerated and more immunogenic compared to SC administration. In conclusion, mpHBV and Heptavax®-II were well-tolerated and elicited satisfactory immune responses for the prevention against hepatitis B virus-associated diseases.